Efektifitas Teknik Pengambilan Keputusan Terstruktur Dalam Proses Pengambilan Keputusan Perusahaan - Jihan Nur Rahmiilah Ayu (Jurnal Akuntansi Dan Manajemen Indonesia (JAMIN), 2022)
Tithe age of time, there is a global change in either the macro or micro order systems that encompass various sectors including business. Environmental uncertainty resulting from changes and era demands leads to complex problems that call for companies to make decisions quickly but in order to tackle them correctly in order to keep the business going. So a company leader would be required to have the ability to make a decision and select the correct decision techniques in the wheel of an organization or company. One well-known model or decision-making technique is the structured or programmed decision-making technique. Structured or programmable decisions are repeated decisions that result in repeated and routine decisions because they are often found in similar situations. While this is a regular or recurring decision, companies must certainly look at and assess just how effective these structured decision making techniques can be. Therefore, researchers are conducting this study using a literature study method in order to see how effective structural decision making techniques can be used